Disturbing effect of cepharanthine on valve interstitial cells calcification via regulating glycolytic metabolism pathways - Xie, Fei; Han, Juanjuan; Wang, Dashuai; Liu, Peng; Liu, Chao; Sun, Fuqiang; Xu, Kang (Frontiers in Pharmacology, 2022)
Osteogenic differentiation of valve interstitial cells (VICs) directly leads to aortic valve calcification, which is a common cardiovascular disease caused by inflammation and metabolic disorder. There is still no ideal drug for its treatment and prevention. The purpose of this study was to explore the effect and molecular mechanism of cepharanthine (CEP), a natural product, on inhibiting the osteogenic differentiation of VICs. First, CCK8 assay was used to evaluate cell viability of CEP on VICs. CEP concentration of 10 μM was the effective dose with slight cytotoxicity, which was used for further study. The alizarin red staining analysis showed that CEP significantly inhibited calcium deposition caused by osteogenic medium related calcification induction. In order to explore the anti-calcification molecular mechanism of CEP, transcriptome and metabolome were synchronously used to discover the possible molecular mechanism and target of CEP. The results showed that CEP inhibited valve calcification by regulating the glycolytic pathway. The molecular docking of CEP and selected key factors in glycolysis showed significant binding energies for GLUT1 (−11.3 kcal/mol), ENO1 (−10.6 kcal/mol), PKM (−9.8 kcal/mol), HK2 (−9.2 kcal/mol), PFKM (−9.0 kcal/mol), and PFKP (−8.9 kcal/mol). The correlation analysis of RUNX2 expression and cellular lactate content showed R2 of 0.7 (P < 0.001). In conclusion, this study demonstrated that CEP inhibited osteoblastic differentiation of VICs by interfering with glycolytic metabolisms via downregulation of the production of lactate and glycolysis-associated metabolites.